2019
DOI: 10.14814/phy2.14237
|View full text |Cite
|
Sign up to set email alerts
|

Changes in joint, muscle, and tendon stiffness following repeated hopping exercise

Abstract: The purpose of this study was to elucidate the mechanisms of decline in joint stiffness after repeated stretch‐shortening cycle exercises according to changes in both muscle‐tendon properties and neuromuscular activities. Eleven males performed fatigue task (5 sets of 50 hopping). Ankle joint stiffness and electromyographic activities (mEMG) of plantar flexor and tibial anterior muscles during drop jump were measured before and after fatigue task. Active muscle stiffness with (100 deg·sec−1) and without (250 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
5
26
0
Order By: Relevance
“…Indeed, Kubo and Ikebukuro (2019) have recently reported a large reduction in the amount of MG fascicle shortening during the braking phase of ankle-joint only DJs after repeated hopping. In particular, at group level the fascicles showed an initial stretch immediately after ground contact ( Figure 1B in Kubo and Ikebukuro, 2019), demonstrating potential for fascicles to be exposed to greater strain as the exercise protocol proceeded. Greater fascicle strain as the exercise task progressed would have led to muscle damage (Lieber and Fridén, 1993;Peñailillo et al, 2015) that has previously been reported after similar fatigue protocols (Miyama and Nosaka, 2004;Ishikawa et al, 2006;Dousset et al, 2007).…”
Section: Muscle Architecture Changes At Restmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, Kubo and Ikebukuro (2019) have recently reported a large reduction in the amount of MG fascicle shortening during the braking phase of ankle-joint only DJs after repeated hopping. In particular, at group level the fascicles showed an initial stretch immediately after ground contact ( Figure 1B in Kubo and Ikebukuro, 2019), demonstrating potential for fascicles to be exposed to greater strain as the exercise protocol proceeded. Greater fascicle strain as the exercise task progressed would have led to muscle damage (Lieber and Fridén, 1993;Peñailillo et al, 2015) that has previously been reported after similar fatigue protocols (Miyama and Nosaka, 2004;Ishikawa et al, 2006;Dousset et al, 2007).…”
Section: Muscle Architecture Changes At Restmentioning
confidence: 99%
“…Briefly, the formula accounts for the perpendicular ground reaction force, the estimated length between the center of the ankle joint (center of the lateral malleolus) and the ball of the foot, and the ankle joint angle at the lowest point (transition from braking to propulsion phase). Ankle joint stiffness was calculated as the change in ankle joint moment divided by the change in ankle joint angle during the braking (eccentric) phase (Kuitunen et al, 2002;Kubo and Ikebukuro, 2019).…”
Section: Performance Measuresmentioning
confidence: 99%
See 3 more Smart Citations